PEMBELAJARAN VOKAL DI SMA PERTIWI 1 PADANG - Rio Zuharmen; Ardipal Ardipal; Syahrel Syahrel (SENDRATASIK UNP, 2013)
Abstract This research aims at describing the vocal practice learning at SMA Pertiwi 1 Padang. This research qualitative research used descriptive analysis method. Techniques of data collection were observation, documentations, and library research. In analyzing data, this research used used learning theory. The analysis was conducted through three steps, they are: identification, classification, and interpretation. Besides, the research also used portfolio containing lesson plan, teaching process, assessment, analysis, and evaluation.